WOMEN AT THE FOUNDATIONS OF THE BRIDGE OF ARTA: CONSTRUCTING DOMESTIC DRAMATURGY IN THE BELLE ÉPOQUE - Ritsatou, Konstantina (ΠΑΡΑΒΑΣΙΣ/PARABASIS, 2025)
During the Belle Époque, when women's emancipation was dynamically advancing in Europe, within just five years, Smaragdo, Flandro, and Smaragda, women of original dramatic production, are successively built into the foundations of «The Bridge of Arta», as happens in the famous folk song which inspired three playwrights. The study illuminates these three women who, until today, remained under the heavy shadow of the master builder, buried in his connections with the Nietzschean theory of the Übermensch and the European avant-garde. In The Bridge of Arta (1905) by Ilias Voutieridis and The Priceless One (1906) by Pantelis Horn, the immured women are the master builder's wives, as described in the ballad. However, both authors place the mother of the immured woman next to her—a character absent from the folk song. Furthermore, Voutieridis complements Smaragdo’s identity: she is also a mother. Only Petros Psiloreitis [Nikos Kazantzakis] in The Master Builder (1910) chooses to place an «unmarried» mistress next to the eponymous character. And, unfortunately for her, the Cretan author does not place the woman who brought her into the world next to her. The study examines, step-by-step, the dialogues of the women whose blood does not bring forth children –a power given to them by nature– but solidifies bridges, as dictated by the patriarchal rule. It observes the breaks with the folk song, the similarities and differences between them, and the dramaturgical manipulations that allow these women to acquire a voice and, in some scenes, claim the center of the plot. We listen carefully to their words, which reveal the different aims of the authors, but in every case, deliver powerful emotional charges to the reader and potential spectator.